Neonatal exposure to low doses of endosulfan disrupts the expression of proteins regulating uterine development and differentiation. - Milesi, Maria Mercedes (2012)
This study investigates the effects of neonatal exposure to low doses of endosulfan on the expression of proteins regulating uterine development and differentiation. Female pups received vehicle, endosulfan (Endo6: 6μg/kg, Endo600: 600μg/kg) or diethylstilbestrol (DES: 0.2μg/kg) from postnatal day 1 (PND1) to PND7. The uterine expression of estrogen receptor alpha (ERα), progesterone receptor (PR), Hoxa10 and alpha smooth muscle actin (α-SMA) was detected by immunohistochemistry on PND8 (neonatal period) and PND21 (prepubertal period), to evaluate acute and short-term responses. ERα, Hoxa10 and α-SMA were induced in the Endo600 group in both ages, while a striking decrease in PR expression was detected in the prepubertal rats following each dose of endosulfan. DES treatment deregulated ERα and Hoxa10 uterine expression at each age. Studies are currently underway to investigate whether the dysregulation of steroid receptors, Hoxa10 and α-SMA observed following neonatal exposure to endosulfan affect uterine functions in adulthood.